RAPID VARIABLES IN THE ORION NEBULA - RIVERA TERRAZAS, LUIS; HARO, G (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1960)
During a study of the Ha emission stars in and near the Orion nebula Haro found a good number of cases where the Haemission line or the continuum varies in intensity strongly suggesting a "Flare" star. As a continuation of this work we have found 7 new st
BOL OBS TONAN TACUB
Keywords: RAPID, VARIABLES, ORION NEBULA; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS